2013
DOI: 10.1074/jbc.m113.496778
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Vertebrate Dihydropyrimidinase and Complexes from Tetraodon nigroviridis with Lysine Carbamylation

Abstract: Background: Lysine carbamylation facilitates metal coordination for enzymatic activities. Results: Structures of dihydropyrimidinase as the apo-and holoenzyme with one and two metals and its substrate/product complexes are determined. Conclusion:The structures reveal four steps in the assembly of the holoprotein with the carbamylated lysine and two metal ions. Significance: The results illustrate how proteins exploit lysines and metals to accomplish lysine carbamylation and enzymatic functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 55 publications
2
28
0
1
Order By: Relevance
“…Carbamylation is also an irreversible non-enzymatic modification process, and its formation process is that the decomposition products of urea react with the N-terminus of the protein or the side chain of lysine residues, which is related to protein aging [65]. Lysine carbamylation can promote the coordination of metal ions to specific enzyme activities [66,67]. It has been reported that the plasma carbamylation levels of patients with elevated urea levels (such as nephropathy) are significantly increased [68].…”
Section: Discussionmentioning
confidence: 99%
“…Carbamylation is also an irreversible non-enzymatic modification process, and its formation process is that the decomposition products of urea react with the N-terminus of the protein or the side chain of lysine residues, which is related to protein aging [65]. Lysine carbamylation can promote the coordination of metal ions to specific enzyme activities [66,67]. It has been reported that the plasma carbamylation levels of patients with elevated urea levels (such as nephropathy) are significantly increased [68].…”
Section: Discussionmentioning
confidence: 99%
“…The chemical mechanism of the binuclear metal center-containing amidohydrolase likely involves three steps: (1) the hydrolytic water molecule must be activated for nucleophilic attack, (2) the amide bond of the substrate must be made more electrophilic by the polarization of the carbonyl–oxygen bond, and (3) the leaving group nitrogen must be protonated as the carbon-nitrogen bond is cleaved [ 38 , 48 ]. This catalytic mechanism is applicable to each member in the cyclic amidohydrolase family [ 41 , 48 , 49 ]. However, a question remains as to why a common mechanism-based inhibitor for these imide-hydrolyzing enzymes, such as imidase, hydantoinase, dihydropyrimidinase, allantoinase, and dihydroorotase, is difficult to find.…”
Section: Discussionmentioning
confidence: 99%
“…许多含有脱氢丙氨酸的肽具有一定的毒 性 [23] , 因此, 发生这种修饰的蛋白质或肽也都具有一 [24] . 赖氨酸氨 基甲酰化可以促进金属离子对特定酶活性的配位作 用 [25,26] . 据报道, 尿素水平升高的患者(例如肾病患者) 的血浆中氨甲酰化的量显著增加 [27] .…”
Section: Figureunclassified